ADHD, Methylphenidate, and Childhood Epilepsy - Rahul Sharma; Sigita Plioplys (Pediatric Neurology Briefs Publishers, 2016)
Investigators from the Department of Functional Neurology, Epileptology and Epilepsy Institute (IDEE), and the Lyon's University Hospital examined the clinical determinants of ADHD severity in children with epilepsy (CWE) along with the response to treatment with methylphenidate (MPH).